Identification of Ethnomathematics of the Toraja Tribe and Its Relationship with Mathematical Concepts in Elementary Schools - Novalia Sulastri; Sefrin S Tangkearung (Universitas Muhammadiyah Enrekang, 2022)
Ethnomathematics is mathematics that exists in the culture. The purpose of this study is to describe the results of identifying ethnomathematics forms of the Toraja tribe and obtaining the results of the analysis of ethnomathematics relationships in the Toraja tribe in accordance with mathematical concepts in elementary schools. The method used is a qualitative method with an ethnographic approach. The data collection techniques carried out in this study were observation, interviews, and documentation. Data analysis in this study includes data reduction, data presentation, as well as drawing conclusions, and verification. The result of this study is that on the activities and artifacts of the Toraja tribal community there are ethnomathematic forms that are related to the mathematical concept in elementary school, namely tombi', the number of gayang in traditional ceremonies is related to integer operations; lola', bombongan, senuan, bingka', sokkong bayu, ma'bugi' movement pattern, ma'badong movement pattern related to the concept of circle; stone burrows, lamba-lamba, ale, la'pa', woven fabrics related to the concept of a rectangle; kandaure and paruki' motifs are related to the concept of rhombus; jipang cakes are related to the concept of cuboid; suke, patti, suling, pompang, gandang, baka, buria' and pa'piong are related to the concept of cylinder; sarong is related to the concept of cone; unuran is related to the concept of a hexagonal prism; songko' relates to the concept of the sphere; limbong pala', kutu', pongo' relates to the concept of measurement and the weaving process is related to the concept of the phytagoras theorem.